Presence of Coxiella burnetii in Airborne Dust Samples from Goat and Sheep Farms in Kerman, Iran - Mohammad Khalili (Journal of Medical Bacteriology, 2016)
Background:  Q fever is a zoonotic disease caused by inhalation of the bacterium Coxiella burnetii. Ruminant livestock are common reservoirs for C. burnetii, and bacteria present in aerosols derived from the waste of infected animals can infect humans. C. burnetii is thought to infect humans primarily via airborne transmission. Methods: 64 environmental swab samples were collected from 24 sheep and goat farms in Southeast Kerman province (Iran). Results:  In this study touchdown nested trans- PCR were used for detection of C. burnetii in environmental samples. We detected C. burnetii DNA in inhalable dust samples collected at 5 farms. Conclusion:  This first report in Iran highlighted presence of C. burnetii in dust originated from goat and sheep farms and that role in human infections with disseminating by wind.